Frailty in outpatients with cirrhosis: A prospective observational study. (29th October 2020) - Román, Eva; Parramón, Marc; Flavià, Montserrat; Gely, Cristina; Poca, Maria; Gallego, Adolfo; Santesmases, Rosalia; Hernández, Elvira; Nieto, Juan C.; Urgell, Eulàlia; Alvarado‐Tapias, Edilmar; Vidal, Silvia; et al.
Abstract: Background and Aim: Frailty is increasingly recognized as a major prognostic factor in cirrhosis in addition to conventional liver insufficiency scores. The aim was to compare the prevalence and characteristics of frailty between patients with cirrhosis and controls, and to analyse its prognostic value. Methods: We included outpatients with cirrhosis and age‐ and gender‐matched non‐cirrhotic controls. Frailty was defined according to the Fried frailty criteria. In patients with cirrhosis, we analysed the ability of the degree of frailty to predict a composite endpoint, consisting of hospitalization, admission to a long‐term care centre, falls or death. Results: We included 135 patients with cirrhosis and 135 controls. The prevalence of frailty was higher among patients with cirrhosis: 35 (25.9%) frail, 74 (54.8%) pre‐frail and 26 (19.2%) robust vs 14 (10.4%) frail, 67 (49.6%) pre‐frail and 54 (40%) robust ( P < .001) in controls. This difference was mainly as a result of decreased muscle strength in patients with cirrhosis. During follow‐up, frail patients with cirrhosis showed a higher probability of composite endpoint, hospitalization and falls than pre‐frail and robust cirrhotic patients but mortality was similar. MELD‐Na score and frailty were independent predictive factors for hospitalization, frailty for falls, and MELD‐Na score and albumin for survival. Vitamin D deficiency and increased cystatin C were associated with frailty. Conclusions: Frailty was more frequent in outpatients with cirrhosis than in controls, mainly because of a decrease in muscle strength, and it could be a predictive factor for hospitalization and falls in these patients.